2021
DOI: 10.1007/s40167-021-00100-1
|View full text |Cite
|
Sign up to set email alerts
|

Distressed but happy: health workers and volunteers during the COVID-19 pandemic

Abstract: During the COVID-19 outbreak, many people rose to the occasion by engaging in volunteerism and health work. We conducted two nationwide surveys in the United States (n = 2931) and China (n = 2793) assessing volunteers' and health workers' levels of mental distress and happiness. In spite of data being collected at different phases of the COVID-19 outbreak and across two different cultures, the results converged. Volunteers and health workers reported higher mental distress (e.g., depression, anxiety, somatizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
(48 reference statements)
3
12
0
1
Order By: Relevance
“…Fourth, and last, but perhaps most important, our serving Civil Protection volunteers displayed a positive, strong sense of help, together with the awareness of their group identity that enables all members to experience a sense of well-being, belonging, fellowship and cohesion. Our findings are not surprising and confirmed recent studies that found that volunteers serving during the COVID-19 pandemic, although initially experiencing distress conditions, were "happy" and satisfied [57]. Compared to the few published studies on volunteer civilians, many studies have been conducted on medical students and future healthcare professionals' volunteering, reporting a sense of giving real aid among the benefits, driven by altruism and the ethical imperative to serve their community [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…Fourth, and last, but perhaps most important, our serving Civil Protection volunteers displayed a positive, strong sense of help, together with the awareness of their group identity that enables all members to experience a sense of well-being, belonging, fellowship and cohesion. Our findings are not surprising and confirmed recent studies that found that volunteers serving during the COVID-19 pandemic, although initially experiencing distress conditions, were "happy" and satisfied [57]. Compared to the few published studies on volunteer civilians, many studies have been conducted on medical students and future healthcare professionals' volunteering, reporting a sense of giving real aid among the benefits, driven by altruism and the ethical imperative to serve their community [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, anxiety response results in a significant decrease in people's prosocial intentions. In fact, evidence shows that COVID-19 volunteers are practically vulnerable to mental distress such as depression, anxiety, and somatization [26,27,36]. Future studies could further explore the role of anxiety in volunteering during COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, volunteering during the COVID-19 pandemic should be one of those high-risk of infection contexts that people may want to avoid. Help-workers and volunteers not only put themselves at risk of infection but also risk undermining their mental health [26]. For example, evidence suggests that volunteers and medical staff suffered more from insomnia, anxiety, depression, and distress [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of regulating the negative emotional impact of a pandemic, the “buffering effect” of resilience as the ability to adapt to adversity, trauma or other major stressors has also been confirmed ( Barzilay et al, 2020 ; Ran et al, 2020 ). Similarly (in relation to the emotional experiencing of the pandemic), more intense direct experience of other aspects of the COVID-19 pandemic, or the “overloading” of one’s own time resources in the form of volunteering also appears to contribute to a higher presence of mental distress ( Mo et al, 2021 ; Zhang et al, 2021 ). Finally, support and clear communication and organization by universities, or lack of it, has been shown to contribute to better/worse mental health of students, as already shown in previous studies ( Magnavita et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%